Analisis Kualitas Website Integrated Lab Journal Menggunakan Webqual Dan Importance Performance Analysis - Agus Mulyanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The Integrated Lab Journal website is an e-journal website published by Sunan Kalijaga Yogyakarta State Islamic University as a medium for scientific papers on laboratory education. This research instrument uses the webqual method which consists of 3 variables, namely usability, information quality, and service interaction quality and 23 indicators. Importance Performance Analysis (IPA) analysis in this study identifies indicators that need to be maintained or improved based on user perceptions and expectations. Webqual Testing involved 100 academics from various universities in Indonesia. The highest gap value is found in the usability variable (u5), which is u5 regarding the appearance of an attractive website with a gap value of -0.830. The results of the IPA analysis show indicators that need improvement, namely u3, i4, i6, and s3. These indicators relate to the ease of navigating the website, relevant information and according to user needs, detailed and complete information, and a sense of security when providing personal information. Indicators that are rated good by the user are in quadrant I, namely u1, u4, u7, u10, i1, i2, i5, s2, and s6. These indicators relate to ease of operation, ease of use, good functioning, effective search, accuracy of information, reliable information, easy to understand information, confidence in publication, and confidence in the editorial process. Keywords : E-journal, Integrated Lab Journal, Webqual, Importance Performance Analysis (IPA)